Mannose binding lectin levels are not related to radiographic damage in ankylosing spondylitis - DİRESKENELİ, RAFİ HANER (SPRINGER, 2010)
In the current study we aimed to investigate the effect of MBL deficiency in radiographic damage of the spine in a large group of AS patients. One hundred and ninety-one AS patients and 85 healthy controls were studied. Disease activity, radiological scores, and demographic features were recorded. MBL levels were measured with standard ELISA kits. Results showed that median MBL levels in AS and healthy controls were 2,530 (range 0-5,861) ng/ml and 3,415 (0-7,950) ng/ml, respectively (p = 0.1). MBL deficiency (< 500 ng/ml) was comparable in both groups (%21.5 in AS, % 17.6; p = 0.5). Disease activity, clinical picture, and therapies were not associated with MBL levels. Both BASRI and mSASSS scores were found similar in AS patients with or without MBL deficiency [BASRI: MBL < 500 ng/ml: 6(2-12), MBL a parts per thousand yen 500 ng/ml: 6(2-12); p = 0.75], [mSASSS: MBL < 500 ng/ml: 3(0-72), MBL a parts per thousand yen 500 ng/ml: 5(0-72); p = 0.81]. We conclude that MBL deficiency prevalence is not increased in AS patients and it is not a cause of a severe radiographic damage.
Keywords: Ankylosing spondylitis; Mannose binding lectin; Radiographic damage; RHEUMATOID-ARTHRITIS; ASSOCIATION